Itinerary of an illusion: life of a layout. (Journal of Parents and Teachers, 2014)
Composing music, playing instruments, singing and finally recording a record is the illusion of many people. However, the layout process is long and complex, as explained step by step in this article.
Keywords: Composing; illusion; music; disk; recording; layout.